Comparison of Shock Absorption and Energy Expenditure between Unilateral Transtibial Amputees Using Jaipur and SACH Feet: A Cross-sectional Analysis - Anand Raja Devaraj Sushama; Jijo Varghese; Thongsuangmung Guite; George Zachariah (Indian Journal of Physical Medicine & Rehabilitation)
Background: Prosthetic feet are crucial in improving the quality of life for lower limb amputees. The most common prosthetic feet used in India are the Jaipur and SACH feet. The choice between these prosthetic feet remains mostly arbitrary. Shock absorption and energy expenditure between these prostheses could be used as the criteria for choosing between them. This study aimed to compare the shock absorption characteristics and energy expenditure of unilateral transtibial amputees using the Jaipur and the SACH feet. Methodology: A cross-sectional observational study was conducted on unilateral transtibial amputees using Jaipur or SACH feet. Peak vertical ground reaction force (VGRF) during heel strike was measured using BTS force plates, and the physiological cost index (PCI) was measured using a Digital Pulse Monitor to assess shock absorption and energy expenditure, respectively. Results: The study found that peak VGRF on heel strike using SACH foot was 1.34, 95% confidence interval (CI) 1.27–1.43, P < 0.001, and that of Jaipur foot was 1.60, 95% CI 1.47–1.80, P < 0.00. This indicated that the SACH foot exhibited superior shock absorption than the Jaipur foot. However, no significant difference was found in energy expenditure between the two groups, as measured by PCI (PCI of SACH foot was 0.33, 95% CI 0.25–0.40 and PCI of Jaipur foot was 0.29, 95% CI 0.24–0.36, P = 0.6). Conclusion: The SACH foot has a better shock absorption character than the Jaipur foot. There is no difference in energy expenditure between users of Jaipur and SACH feet.